2019
DOI: 10.1002/advs.201900137
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical β‐Selective Hydrocarboxylation of Styrene Using CO2 and Water

Abstract: in enediolate intermediates. [1] Recently, a similar mechanism of CO 2 insertion at the unsaturated carbon bond has been adopted in the synthesis of carboxylic acids employing alkynes, [2] α-olefins [3] and internal alkenes as substrates. [4] These methods enabled CO 2 to be harnessed as a renewable one-carbon building block; however, the valorization of CO 2 is still challenging because the gas is thermodynamically and kinetically stable. [5] Consequently, numerous advances in chemical carboxylation using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 45 publications
4
62
0
1
Order By: Relevance
“…As 3-arylpropionic acids also are valuable compounds (Figure 1a), 35,[43][44][45] we further investigated the visible-lightdriven photocatalyst-free anti-Markovnikov hydrocarboxylation of styrenes (Figure 2). Under slightly modified reaction conditions (Condition B: p-t BuC 6 H 4 SH is used instead of 2,4,6-triisopropylthiophenol in Condition A), diverse styrenes bearing either electron-neutral (3a-3c, 3i, and 3m) or electron-donating (3d, 3f, and 3j) groups on the arene moiety all reacted smoothly to afford the desired products 4 in moderate to good yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As 3-arylpropionic acids also are valuable compounds (Figure 1a), 35,[43][44][45] we further investigated the visible-lightdriven photocatalyst-free anti-Markovnikov hydrocarboxylation of styrenes (Figure 2). Under slightly modified reaction conditions (Condition B: p-t BuC 6 H 4 SH is used instead of 2,4,6-triisopropylthiophenol in Condition A), diverse styrenes bearing either electron-neutral (3a-3c, 3i, and 3m) or electron-donating (3d, 3f, and 3j) groups on the arene moiety all reacted smoothly to afford the desired products 4 in moderate to good yields.…”
Section: Resultsmentioning
confidence: 99%
“…17,18,22,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Notably, Iwasawa pioneered this strategy by realizing the hydrocarboxylation of alkenes with Markovnikov regioselectivity via visible-light photoredox/Rh dual catalysis. 27,41 Besides Markovnikov selectivity, König et al 35 also realized a novel hydrocarboxylation of styrenes with anti-Markovnikov regioselectivity 26,[43][44][45] via photoredox/ nickel dual catalysis. In these cases, both photocatalysts and transition-metal catalysts are indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…[69] The activation of CO 2 and olefin can also occur simultaneously, as reported in other works. [70][71][72] In general, the reduction of alkenes and olefins is the preferred approach. Buckley and coworkers reported an electrosynthetic approach using stainless steel as cathode and triethanolamine c) Reproduced with permission.…”
Section: The Electrocarboxylation Reaction Of Olefins or Alkynesmentioning
confidence: 99%
“…c) Reaction mechanism of electrochemical β-selective hydrocarboxylation of styrene. Reproduced with permission [70]. Copyright 2019, Wiley.…”
mentioning
confidence: 99%
“…Iron-catalyzed hydrocarboxylation, as reported by Thomas et al, is shown in Scheme 4 [ 27 ]. Although hydrocarboxylation of styrene was expected to introduce the ibuprofen skeleton, the regioselectivity hampered it [ 28 ]. However, the highly selective addition of CO 2 was possible by employing an iron catalyst and pyridine ligand 15 .…”
Section: Recent Synthetic Advances In Ibuprofenmentioning
confidence: 99%